Exploring Chatgpt’s Efficacy in Identifying Potential Business Partners: A Comparative Study - Prohorovs Anatolijs; Dalal Surjeet; Radulescu Magdalena (Economics and Culture)
This study aims to evaluate the effectiveness of using ChatGPT for a practically important but under-researched task in the scientific literature: the preliminary search and identification of potential business partners or counterparties.